Entrepreneurial Activity, Market Orientation, Investment Attractiveness and Transaction Costs for Enterprises in Local Development Context - Pilewicz, Tomasz; Derlukiewicz, Niki; Mempel-Śnieżyk, Anna; Zdon-Korzeniowska, Małgorzata (Regional Barometer. Analyses & Prognoses, 2018)
The goal of the paper is to explore phenomena of entrepreneurial activities and market orientation of local governments, and also to identify a relation between these phenomena and investment attractiveness of local units and transaction costs for entrepreneurs and investors that authorities of local units might impact. We performed Boolean key word and subject term searches of selected scholar databases between 21 and 24 July 2017. It enabled us to identify less proliferated aspects of local development, which we deepened our knowledge of through systematic literature review aiming to reach the purpose of the paper. Entrepreneurial activities and the market approach of local units are widely explored in scientific research literature, but investment attractiveness of local units and their impact on transaction costs for enterprises are less represented. We present relations between investment attractiveness and transaction costs for enterprises with entrepreneurial activities and market orientation. There are actions local governments can undertake to impact investment attractiveness of local units and transaction costs for enterprises to stimulate the local development process. This work indicates the importance of increasing investment attractiveness of local units by local governments and lowering transaction costs for enterprises in the local development process.